Crises, Covid-19, and Entrepreneurship. (May 2023) - Batjargal, Bat; Jack, Sarah; Mickiewicz, Tomasz; Stam, Erik; Stam, Wouter; Wennberg, Karl
This virtual special issue includes research on the effects of crises, in particular the COVID-19 pandemic, on entrepreneurship, and entrepreneurial responses to deal with consequences of crises. This issue highlights how crises affect entrepreneurs' well-being and reinforce the importance of agency of entrepreneurs and other citizens. The special issue also highlights the need for resilience; the ability of entrepreneurs, organizations, and economies to absorb and adapt to shocks; and how it can be strengthened. We discuss the importance of data in times of crisis and the greater need for engaged scholarship.